Video and Theatre: An Analysis fo Videoscen Projects - Sedeño-Valdellos, Ana; Gaona Pisonero, Carmen; Linares Pedrero, Agustin (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
Video scene, as an integrative concept linking theatre and video materials, constitutes a new dimension of audiovisual production as one further component within the mise-en-scène. This article proposes an analysis of works belonging to contemporary Spanish theatre that incorporate video, with the aim of characterising video-scenic production through a study of its technical options, functions and uses. The conclusions address the various configurations that deepen the different degrees of integration of video within the dramatic proposal of the scenic projects.